Acceptability of Single-dose Clindamycin Gel for Bacterial Vaginosis: A Randomized Controlled Trial - Mauck, Christine; Hillier, Sharon L.; Gendreau, Judy; Dart, Clint; Wu, Hongsheng; Chavoustie, Steven; Sorkin-Wells, Valerie; Nicholson-Uhl, Clifton Scott; Perez, Brandon; Jacobs, Mark; Zack, Nadene; Friend, David (Clinical therapeutics, 2023)
The goal of this study was to assess the acceptability of a single-dose bioadhesive 2% clindamycin vaginal gel for bacterial vaginosis (BV). This double-blind, placebo-controlled, randomized study compared a new clindamycin gel with placebo gel (2:1 ratio). The primary objective was efficacy; secondary objectives were safety and acceptability. Subjects were evaluated at screening, days 7 to 14 (Day 7–14), and days 21 to 30 (test-of-cure [TOC]). An acceptability questionnaire with 9 questions was administered at the Day 7–14 visit, and a subset of questions (#7–#9) was asked again at the TOC visit. At Visit 1, subjects were provided with a daily electronic diary (e-Diary) to collect information regarding study drug administration, vaginal discharge, odor, itching, and any other treatments used. Study site staff reviewed e-Diaries at the Day 7–14 and TOC visits. A total of 307 women with BV were randomized to treatment (204 to the clindamycin gel group and 103 to the placebo gel group). Most (88.3%) reported at least one previously diagnosed BV episode, and more than one half (55.4%) had experience with other vaginal treatments for BV. At the TOC visit, almost all (91.1%) of the clindamycin gel subjects described their overall experience with the study drug as “satisfied” or “very satisfied,” 95.8% indicated that they would be “likely” or “very likely” to use the product again if it became available after the study and they had BV again, and 93.7% would be “likely” or “very likely” to recommend their treatment to a friend who had BV. Almost all (90.2%) clindamycin-treated subjects responded that application was “clean” or “fairly clean,” as opposed to “neither clean nor messy,” “fairly messy,” or “messy.” Although 55.4% experienced leakage in the days after application, only 26.9% of those indicated that it was bothersome. Subjects receiving clindamycin gel also reported improvement in both odor and discharge, commencing shortly after dosing and continuing through the assessment period, regardless of whether they met the critical cure criteria. A single dose of a new bioadhesive 2% clindamycin vaginal gel showed rapid resolution of symptoms and was highly acceptable as a treatment for bacterial vaginosis. ClinicalTrials.gov identifier: NCT04370548.